Human resources as the development of rural areas (Research Bulletins of the Faculty of Economic Sciences, 2021)
Near 40% of the aggregate number of Poland’s inhabitants live in rural areas. For thestructure of age, profitable transformations of other structures and coefficients ofreproduction introduced in this elaboration – demographic resources of rural areasdetermine the significant development potential. We ought to do our best, to make thefull use of it. Versatile rural development should be the main direction of the activation
Keywords: uman resources, the demographic structure, the social-professionalstructure of population, rural areas, the development potential